Facility manager competencies for building performance at public building / Siti Nurfaqiha Adila Kamaluddin - Kamaluddin, Siti Nurfaqiha Adila (2021)
Facility manager has so many competencies in manage and also handling the facilities that provided in any type of building. This research is focus on the how the facility manager’s competencies play an important role in order to make sure that the building can perform well. There are different types of building either it is private building or public building. This study is focus on public buildings which are public hospital, shopping mall, office building and also educational building. Hence, the study is being carried out and the aim of this research is to study the competencies of the facility manager to manage the facilities management in the building. There are three objectives of this study which are to identify the competencies of facility manager in public buildings, to understand the relation of facility manager competencies with the building performance and to suggest the recommendations to facility manager on how to improve their competencies. This research was carried out in Malaysia and there are two different methods for data collection which were primary data collection and also secondary data collection. For primary data collection method, questionnaires have been distributed to gain the data from the respondents. As for the secondary data collection method, the data obtained from various sources such as articles, previous research papers, websites and also biographies. The data analysed by using the SPSS software where the descriptive analysis is used. based on the data analysis and findings made, it shows that most of facility managers are aware with the competencies that they need to practice and develop. Furthermore, the findings also show that most of the respondents are agreed that all the competencies are affect the performance of the building and it does play important role for the building to perform better.